Produtos à base de própolis (LLOS) na dieta de bovinos mestiços não castrados em confinamento - Aguiar, Sílvia Cristina de (2009)
The objective was to evaluate performance, total digestibility, efficiency of microbial synthesis and carcasses characteristics of feedlot cattle fed ration with 50%:50% forage: concentrate with propolis based products (LLOS). Twenty seven crossbred young bulls were used, with 320.69 ± 27.89 kg of body weight in a randomized experimental design, divided into three treatments: control treatment without propolis addition (CON) and two treatments with propolis based products (LLOS) with different concentrations (LLOSC1 and LLOSC1+). The diet was formulated with 70.2% of TDN and 13.5% CP. To determine the total digestibility, the indigestible dry matter was used as an internal indicator while microbial production was estimated from purine derivatives in urine, collected by the spot method. The evaluated carcass characteristics were: hot carcass weight, hot carcass dressing, conformation, Longissimus muscle area, fat depth, color, texture, marbling, pH, beef round thickness and percentages of muscle, bone and fat. The studied variables were submitted to a variance analysis considering 5% of probability. The different treatments did not influence on performance, total digestibility of DM and nutrients or on efficiency of microbial synthesis. The characteristics of carcass were not affected by experimental treatments either. Thus, it is primordial the accomplishment of other researches in this area, due to the lack of consistent data concerning propolis action on animal performance and meat quality.